The contribution of production scheduling rules to activating cyber production requirements: An exploratory study at the General Company for Electrical and Electronic Industries – Baghdad (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to diagnose the contribution of production scheduling rules in activating cyber production requirements and to determine the implications of this relationship at the level of the General Company for Electrical and Electronic Industries in Baghdad as a field of research, as manufacturing companies today face a major challenge represented by increasing complexity and responding to dynamic changes in addition to achieving short delivery times. As planning, control and scheduling mechanisms cannot deal efficiently under complex, dynamic and unexpected circumstances, this requires a move towards creative activities and problem solving using collaborative decision-making mechanisms between human and artificial intelligence. Therefore, a move was made towards creating requirements for the cyber production system that would have a positive impact. On artificial and human intelligence through trustworthy interaction and integration into the cyber production system. The research problem is demonstrated by answering the following question: Do production scheduling rules affect the activation of cyber production requirements in the researched company? To answer the research questions, reliance was placed on the descriptive analytical approach and on tools and methods for collecting data and information, represented by personal interviews and a questionnaire form that was distributed to 60 individuals working in the company, the research sample. The importance of the research is evident through its treatment of two variables that have become of great importance in our world today, as they It dealt with production scheduling as a tool for allocating resources and loading according to its rules, in addition to its endeavor to activate the requirements of cyber production, which is one of the applications of the fourth generation of industry and is consistent with artificial intelligence methods. In order to analyze the results of the practical side, a set of hypotheses were developed and tested in the company in the field of research using the statistical program. (SPSS VE 26) In addition to a number of statistical methods, the research reached a set of conclusions, the most prominent of which is: The existence of a significant correlation was achieved between production scheduling in terms of its rules (in general and individually) and cyber production in terms of its requirements (in general) in the company, the field of research, and this explains that the company’s management It was able to employ its rules to process requests and arrange work in an effort to enhance cyber production requirements. He presented a set of proposals, the most prominent of which are: increasing the company’s management’s interest in the field of research in production scheduling rules, deepening their importance, and enhancing investment in other rules according to customer requests by making adjustments to scheduling from time to time to avoid delays. In delivering products to customers.